Protective Effect of Mannitol on Cisplatin-Induced Nephrotoxicity: A Systematic Review and Meta-Analysis - Li, Songtao; He, Xiuyun; Ruan, Linjie; Ye, Ting; Wen, Yulong; Song, Zhihua; Hu, Siying; Chen, Yu; Peng, Bo; Li, Shijie (Frontiers in Oncology, 2021)
Introduction Cisplatin, a chemotherapeutic drug, is widely used for the treatment of various malignant tumors with good effects. However, cisplatin-induced nephrotoxicity is a major dose-limiting factor and a significant adverse event. Mannitol is used to reduce cisplatin-induced nephrotoxicity, which is controversial. This study aimed to evaluate the efficacy and safety of a hydration regimen containing mannitol against cisplatin-induced nephrotoxicity through a meta-analysis. Methods Potential records from PubMed, EMBASE, Cochrane Library, and ClinicalTrials that met the inclusion criteria were included from inception to May 2021. Cochrane Collaboration tools were used to assess the risk of bias in the included studies. Jadad’s and NOS scores were applied to assess the quality of randomized controlled trials (RCTs) and case-control studies. A random-effects model or fixed-effects model was used depending on the heterogeneity. Subgroup analyses were performed to evaluate the potential study characteristics. The pooled odds ratios (ORs) and 95% confidence intervals (CIs) were evaluated. Results Four RCTs and seven case-control studies involving 4168 patients were included. Pooled results showed that mannitol use could reduce the incidence of cisplatin-induced nephrotoxicity (OR = 0.66, 95% CI [0.45–0.97], p = 0.03), especially reducing grade 3 nephrotoxicity events according to CTCAE 4.0 (OR = 0.37,95% CI [0.16–0.84]). Moreover, mannitol use was not significantly associated with creatinine clearance, serum creatine, and electrolyte disturbance (p > 0.05). Gastrointestinal cancer (OR = 0.36, 95% CI [0.15–0.83], p = 0.02) and urinary tract cancer (OR = 0.32,95% CI [0.14–0.73], p = 0.007) may be more sensitive to mannitol, although the test for overall effect was significantly different (OR = 0.66, 95% CI [0.49–0.89], p = 0.007). For patients with diabetes and hypertension, mannitol may worsen renal function (OR = 1.80, 95% CI [1.18–2.72], p = 0.006; OR = 2.19, 95% CI [1.50, 3.19], p < 0.0001, respectively). Mannitol may have a better protective effect when doses of mannitol were ≥ 25 g (OR = 0.58, 95% CI [0.39–0.88], p = 0.01) and doses of cisplatin < 75 mg/m2 (OR = 0.59, 95% CI [0.36–0.94], p = 0.03). It revealed that mannitol use was likely to cause nausea or vomiting (OR = 1.86, 95% CI [1.20–2.89], p = 0.006). Conclusion Current evidence revealed that mannitol was an effective and safe drug to reduce cisplatin-induced nephrotoxicity events, especially Grade 3 events. However, it may cause more nausea/vomiting events and deteriorate renal function in patients with diabetes or hypertension. We also found that mannitol had the best effect when mannitol was ≥ 25 g in total or cisplatin was < 75 mg/m2. Meanwhile, mannitol may have a better effect on gastrointestinal and urinary tract cancers. Systematic Review Registration crd. york. ac. uk/PROSPERO, CRD 42021253990